Performance, Competence, Job Satisfaction, and Financial Compensation of Cosmetics Salesforce during the COVID-19 Outbreak - Bambang Dwi Suseno; Indah Hartini Sofa; Mohammad Tri Widayanto; Basrowi Basrowi (Shirkah: Journal of Economics and Business, 2022)
The COVID-19 pandemic caused a decrease in sales turnover for the cosmetic industry, causing salesforce performance to be unsatisfactory. The study developed a model to improve the performance of the cosmetics industry in Banten Province of Indonesia. This quantitative study employed SmartPLS 3.3.2 version to analyze the data obtained from 120 respondents through observations and questionnaire. The results of the empirical model with SEM-PLS revealed that competence has a significant positive effect on financial compensation, competence has a significant positive effect on salesforce job satisfaction, salesforce job satisfaction has a significant positive effect on salesforce performance, financial compensation has no effect on salesforce performance, and salesforce performance has no effect on financial compensation. It is recommended that the cosmetic industry recalculate the amount of compensation appropriately according to measurable performance to yield an impact on salesforce performance. This study highlights the importance of competence-based compensation for fostering self-improvement of employee.